Disseminated leishmaniasis in a four-year-old child in Yaoundé, Cameroon - Mah, Evelyn Mungyeh; Chiabi, Andreas; Atangana, Paul; Nguefack, Seraphin; Mbassi, Awa HD; Nzedjom, Celestine; Tietche, Felix; Tetanye, Ekoe (The Turkish Journal of Pediatrics, 2011)
Leishmaniasis is a disease caused by a protozoan parasite of the genus leishmania with worldwide distribution and is transmitted to man by phlebotomine sand flies. The clinical presentation could range from a single cutaneous ulcer to disseminated leishmaniasis. We report the case of a four-year-old boy admitted to our hospital with ulcers, wasting, progressively distending abdomen, and fatigue evolving for about two months. On admission, he was febrile and pale, with diffuse oozing wet ulcers on the limbs and face, hepatosplenomegaly, and enlarged inguinal lymph nodes. The complete blood count revealed pancytopenia with low reticulocyte count, and serum protein electrophoresis showed hypoalbuminemia and hypergammaglobulinemia. Skin biopsy revealed amastigotes in phagocytic cells. The above findings suggested cutaneous and visceral localization of the leishmania; however, the parents absconded with the boy just when treatment was instituted, believing that the child was bewitched. The outcome is expected to be fatal visceral involvement.